The genus Litophyton Forskål, 1775 (Octocorallia: Alcyonacea: Nephtheidae) from Australia - van Ofwegen, Leen P. (Zootaxa, 2020)
The Litophyton species of Australia are described. Of the 33 species dealt with three were previously described and 30 are considered new. For convenience the species described are divided into five distinct morphological groups. The new species are compared with previously described species from neighbouring Indonesia. L. pyramidalis (Kükenthal, 1895) is synonymized with L. elongatum (Kükenthal, 1895).